Nelayan dan Perilaku Konsumtif (Studi Etnografi pada Masyarakat Kecamatan Muncar Banyuwangi) - Anis Kumalasari; Niken Eriana Azzahra Fauzi; Fayza Jasmine Oktsferly (Universitas Katolik Widya Karya Malang, 2023)
The fishing community in Kedungrejo Village, Muncar District, is close to the consumerist lifestyle. Each of the existing elements creates its own reflection, from skipper fishermen, labor fishermen to factory employees. In short, this research was conducted to describe the lifestyle that is formed in fishing communities, especially in Kedungrejo Village, Muncar District. This study uses a qualitative approach that explains the phenomenon descriptively using observation, interviews, and documentation. The research results obtained in this study indicate that the fishing community in Kedungrejo Village, Muncar District, has a consumptive lifestyle. This shows that the community buys products or luxury goods to maintain prestige in the surrounding environment. Moreover, they buy things based on their desires. The skipper fishing community, which is seen as being in the position of the upper social layer, will try to highlight the identity that is considered to have wealth and power. This study uses the theory of consumerism put forward by Jean Baudrillard which assumes collective individual identity based on commercial interests and not on utility. Just as society represents a need, consumerism makes individual/group behavior believe in the existence of a symbol of power in controlling a certain item.